Responsabilização política nos estados brasileiros: o voto econômico nas eleições para governador - Barone, Leonardo Sangali (2009)
The main purpose on this research is to examine if brazilian electors hold state governors and their parties responsible for local public policies after the transition to democracy, more specifically from 1990 on. It was tested if the probability of reelection in state elections is influenced by subnational economic performance, national economic performance or none of them. Using theoretical models derived from economic voting theory, it was tested if any of the two accountability patterns pointed by the literature exists: retrospective subnational economic voting ou national referendum. Also the relationship between reelection and fiscal performance was explored. Finally, it was tested the conditional effects of the differences of economic structure and autonomy from national government between brazilian states on economic voting. The results point that brazilian electorate hold state governors accountable for unemployment depending on the autonomy of the state from the federal government, confirming the existence of a retrospective economic voting behavior and rejecting the national referendum thesis. States that depend more on fiscal transfers from national government punish governors for high levels of unemployment. Also the fiscal performance seems to be another important factor to explain reelection in state elections. Fiscal surplus in election years is rewarded by electors, against the interpretations that in new democracies politicians can improve electoral performance by raising public expenditure.